2019
DOI: 10.1371/journal.pone.0209646
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone added to local anesthetics in ultrasound-guided transversus abdominis plain (TAP) block for analgesia after abdominal surgery: A systematic review and meta-analysis of randomized controlled trials

Abstract: ObjectiveTo evaluate the analgesic efficacy of dexamethasone added to local anesthetics in ultrasound-guided transversus abdominis plane (TAP) block for the patients after abdominal surgery.MethodsPubMed, CENTRAL, EMBASE, Web of science were searched to identify eligible randomized controlled trials (RCTs) that compared dexamethasone added to local anesthetics in ultrasound-guided TAP block with control for postoperative analgesia in adult patients undergoing abdominal surgery. Primary outcomes included postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 53 publications
(80 reference statements)
1
26
1
2
Order By: Relevance
“…A systematic review and meta-analysis of randomized controlled trials in 2015 by Zhang D and colleagues showed that addition of Dexamethasone to local anesthetics in ultrasound guided TAP block was a safe and effective strategy for postoperative analgesia in adult patients undergoing abdominal surgery. 10 A systematic review for randomized controlled trials by Fusco P et al, that assessed the efficacy of ultrasound (US) guided TAP block following cesarean delivery and concluded that controversy surrounds the utility of USguided TAP block in cesarean section, evidence suggests that when correctly executed as part of a multimodal analgesic regimen, TAP block may reduce postoperative opioid consumption and opioid-related side effects, improving postoperative pain control and patient satisfaction. 11 In our study we observed that duration of analgesia was significantly higher in patients who received bupivacaine along with dexmedetomidine in comparison to the patients who received bupivacaine alone or with dexamethasone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis of randomized controlled trials in 2015 by Zhang D and colleagues showed that addition of Dexamethasone to local anesthetics in ultrasound guided TAP block was a safe and effective strategy for postoperative analgesia in adult patients undergoing abdominal surgery. 10 A systematic review for randomized controlled trials by Fusco P et al, that assessed the efficacy of ultrasound (US) guided TAP block following cesarean delivery and concluded that controversy surrounds the utility of USguided TAP block in cesarean section, evidence suggests that when correctly executed as part of a multimodal analgesic regimen, TAP block may reduce postoperative opioid consumption and opioid-related side effects, improving postoperative pain control and patient satisfaction. 11 In our study we observed that duration of analgesia was significantly higher in patients who received bupivacaine along with dexmedetomidine in comparison to the patients who received bupivacaine alone or with dexamethasone.…”
Section: Resultsmentioning
confidence: 99%
“…A USG guided TAP block was given using linear probe (6)(7)(8)(9)(10)(11)(12)(13) in all groups with respective drug solutions. 23 G spinal needle was advanced by ultrasound guided in plane technique at the anterior axillary line between the 12 th rib and iliac crest with umbilicus at the center and exact location of the needle tip in a plane between internal oblique muscle, transverse abdominis muscle was identified with 1ml of normal saline.…”
Section: Methodsmentioning
confidence: 99%
“…Systematic review had shown a single dose of intravenous dexamethasone could decrease postoperative pain with no increase in infection or delayed wound healing 11 and adding dexamethasone to local anaesthetics in trans versus abdomen is plane block could decrease opioid consumption and prolong the time to first request for additional analgesics. 12 It could also decrease the incidence of postoperative nausea and vomiting.…”
Section: Discussion Factors Affecting Overall Satisfactionmentioning
confidence: 99%
“…Цікаво також, що периневральне введення зменшує частоту післяопераційної нудоти та блювоти. Недавній метааналіз дев'яти рандомізованих клінічних випробувань за участю 575 пацієнтів з дексаметазоном, які використовувались при TAP-блоку, показав зменшення післяопераційної нудоти і блювоти [73].…”
Section: оглядunclassified